The Dead Sea Scrolls and the Bible. By James C. Vanderkam - Salvesen, Alison ca. 20./21. Jh. (The journal of theological studies, 2014)
James C. Vanderkam presented the substance of this highly lucid book as his Speaker’s Lectures in Biblical Studies in Oxford in 2009: the present reviewer had the privilege of hearing them, and the lectures themselves were similarly models of clarity. Vanderkam succeeds in covering major topics in Qumran in relation to wider biblical scholarship without overwhelming the non-specialist reader with detail. He starts with the ‘biblical’ scrolls from the Judean Desert, outlining their significance for our understanding of the development of the Masoretic Text (modern editions of MT being based on manuscripts a thousand years younger than the scrolls).